Legal Protection of The Patient in The Event of Occurrence The Misdiagnosis Is Connected With Law Number 8 Of 1999 Consumer Protection And Law Number 29 Of 2004 Concerning The Practice Of Medicine (Case Study Of High Court Decision DKI Jakarta Number: 624/Pdt/2019/ PT. DKI) - FEBRIYANTI, Ninthiya Dwi (Indonesia Strategic Sustainability, 2023)
Purpose:A patient is someone who needs health services or medical services in a hospital. In medical services, it does not rule out the possibility of an error or negligence. Mistakes or negligence made by health workers in carrying out their duties and profession can have fatal consequences, both on the body and soul of the patient, in this case, of course, it is very detrimental to the patient. Therefore, legal protection is needed for patients and accountability of health workers for losses suffered by patients.Methodology:The data collection techniques in the form of document studies. The data obtained is then processed and compiled systematically, then analyzed qualitatively.Findings:The author has the purpose of this study, first to know and examine the legal protection of patients in Law Number 8 of 1999 concerning Consumer Protection and Law Number 29 of 2004 concerning Medical Practice, and the second author examines the legal responsibility of doctors in the event of a misdiagnosis in case number 624 / PDT / 2019 / PT. DKI.Implication:Protection of patients in the event of misdiagnosis is regulated in several laws and regulations, namely in Article 1365 of the Civil Code, Law Number 8 of 1999 concerning Consumer Protection and Law Number 29 of 2004. The form of legal responsibility of doctors in the event of a misdiagnosis can be divided into ethical responsibility and legal responsibility. Legal responsibility can also be divided into administrative responsibility, criminal responsibility and civil responsibility.